Literary Arpilleras: Textiles as Place-Based, Creative Pedagogy. Issue 1 (14th September 2022) - Clark, Fiona
This article is a reflection on the experience of using textile making, arpilleras, as a creative practice to stimulate engagement with literature and the lived environment in a course on Latin American literature. The discussion will illustrate how, by recognising the body as another place of learning, this approach can help students engage at a deeper and more personal level with ecological fiction and relate their reading to personal experience. Textile making as place-based pedagogy recognises the body as another place of learning & engages students with Latin American fiction.